Rethinking the Dialogue Between the Verbal and the Visual Methodological Approaches to the Relationship Between Religious Art and Literature (1400-1700) - Falque, Ingrid; Guiderdoni, Agnès (BRILL, 2023)
Intro -- Contents -- Illustrations -- Notes on Editors -- Notes on Contributors -- Chapter 1 Introduction -- Chapter 2 Framing the Text-Image Relationship(s) in Henry Suso's Exemplar -- Chapter 3 How to Read the Drawings of Gielis vander Hecken (1491-1538) -- Chapter 4 The Adventures of the Soul in a Wonderful Emblematic Manuscript of the Belgium Royal Library -- Chapter 5 Sese oblectari in dies: Tropes of Materiality and Artisanship in the Paradisus precum selectarum (1610) of the Cistercian Sub-prior Martin Boschman -- Chapter 6 "Hidden Sons", Baptism, and Vernacular Mysticism in Rogier van der Weyden's St. John Triptych -- Chapter 7 The Art of Observance. Jan Provoost's Diptych of a Franciscan Friar as an Exponent of the Spirituality and Position of the Franciscan Order in the Low Countries, c.1520 -- Chapter 8 Jan Brueghel the Elder's First Paradise Landscape (1594) -- Chapter 9 Liber idiotae or lingua universalis? The Language of Images in 17th Century Jesuit Literature -- Index Nominum.
Description based on publisher supplied metadata and other sources
Keywords: Geschichte 1300-1700; Geschichte 1400-1700; Text; Illustration; Buchmalerei; Bild; Literatur; Religiöse Kunst; Electronic books; Aufsatzsammlung; Konferenzschrift -- 20.06.2013-22.06.2013 -- Leiden